Secondary Metabolites of Nicotiana tabacum and Their Biological Activities: A Review - Putri, Devi Anggraini; Solihah, Riyadatus; Oktavia, Rianur; Anggraini, Dwi Aprilia; Fatmawati, Sri (The Journal of Pure and Applied Chemistry Research, 2022)
Nicotiana tabacum (tobacco) is one of the most commercially agricultural crops in the world. Indonesia is one of the top ten tobacco producing countries in the world since 1990â€™s. Based on literature studies, tobacco has the main secondary metabolites such as cembranoids and flavonoids. They have fine biological activities as antiviral, antimicrobial, antioxidant, anti-HIV, anti-proliferative, anti-inflammatory, anti-parasitic, anti-termite, and cytotoxicity effects. Therefore, N. tabacum is potential for further investigation on natural products research. This review aims to provide scientific evidences related to structure activity relationship between secondary metabolites and biological activities of N. tabacum.Â